Factors Affecting Consumers' Behavioural Intention Towards Apparel Stores: A Test of the Mediating Role of Brand Satisfaction - (:unkn) unknown (INST CHEMICAL FIBRES, 2013)
The research studied the factors that affect consumers' behavioural intention towards apparel stores. Three different aspects of behavioural intention were examined: consumers' purchase intention (PI), willingness to pay more (WPAY), and brand recommendation (RECM). Specifically the authors propose a model in which consumer satisfaction with the store brand mediates the effects of attitude towards sales personnel and the convenience of the store's payment conditions or options on PI, WPAY, and RECM. The relationships hypothesized in the model were tested using two apparel store brands familiar to consumers in the city of Istanbul, Turkey. All findings were in favour of the model proposed for both apparel store brands studied, which were either a sample of men or women.
Keywords: satisfaction; willingness to pay more; purchase intention; recommendation; payment conditions; attitude towards sales personnel